Correlation and Improvement of Bimetallic Electronegativity on Metal–Organic Frameworks for Electrocatalytic Water Oxidation. Issue 10 (4th May 2021) - Ying, Meihui; Tang, Rui; Zhao, Shenlong; Yang, Wenjie; Liang, Weibin; Zhang, Xingmo; Yang, Guizeng; Zheng, Rongkun; Pan, Haibo; Liao, Xiaozhou; Huang, Jun
Abstract : Oxygen evolution reaction (OER) plays a critical role in many renewable energy technologies including electrolyzers and rechargeable metal–air batteries. However, the sluggish kinetics of OER catalysts seriously impedes the efficiency of these aforementioned clean devices. Herein, a series of bimetallic metal–organic frameworks (MOFs) with tunable electronegativity (metal ionic electronegativity [MIE]) are prepared by precisely controlling the metal composition for efficient OER. Moreover, an experimental result‐derived volcano plot is first unveiled by presenting the correlation of the MIE and OER kinetic rate (Tafel slope) on the surface of the MOFs‐based electrocatalysts. Remarkably, a Ni0.9 Fe0.1 MOF fabricated and based on the proposed electronegative equilibrium rationales, delivers a low overpotential of 206 mV at 10 mA cm −2 and 270 mV at 50 mA cm −2 along with a long‐term stability in 1 m KOH, superior than the previous reported catalysts. The excellent performance is ascribed to the MIE‐induced interface charge transfer resistance and intermediate adsorption resistance adjustment. The second metal introduction causes the formation of unsaturated metal sites during the electronegative equilibrium process, leading to adjustable OER kinetic rate. These findings pave the way to designing highly active MOF‐based OER catalysts. Abstract : A descriptor based on the metal ionic electronegativity (MIE) of the bimetallic metal–organic frameworks (MOFs) is developed to screen MOFs‐based electrocatalysts for efficient oxygen evolution reaction (OER). A volcano plot is unveiled by presenting the correlation of the MIE and OER kinetic rate on the material surface. A predicted Ni0.9 Fe0.1 MOFs confirmed the excellent consistence with the theoretical prediction.